2005
DOI: 10.1097/01.mnm.0000170937.90958.22
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based assessment of spinal tap test-induced regional cerebral blood flow changes in normal pressure hydrocephalus

Abstract: According to SPM analysis, gait improvement at the spinal tap test in patients with NPH syndrome is associated with an rCBF increase localized in the bilateral dorsolateral frontal and left mesiotemporal cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
2
8
0
1
Order By: Relevance
“…The wider activation associated with DO might reflect simultaneous pelvic floor contraction against DO in order to maintain urinary continence 35. Previous studies have shown hypoperfusion in the frontal lobe in NPH patients using PET,13–15 SPECT,16–18 and perfusion‐weighted MRI,19 most of which are bilateral. However, using bladder function‐related perfusion analysis in the present study, the right frontal cortex showed deactivation more than the left.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wider activation associated with DO might reflect simultaneous pelvic floor contraction against DO in order to maintain urinary continence 35. Previous studies have shown hypoperfusion in the frontal lobe in NPH patients using PET,13–15 SPECT,16–18 and perfusion‐weighted MRI,19 most of which are bilateral. However, using bladder function‐related perfusion analysis in the present study, the right frontal cortex showed deactivation more than the left.…”
Section: Discussionmentioning
confidence: 99%
“…Recent functional neuroimaging, that is, positron emission tomography (PET), in normal volunteers has shown that the anterior cingulate, prefrontal cortex and insula are activated in response to bladder filling as compared with an empty bladder 10–12. Although NPH is a diffuse brain disease with dilated ventricles, hypoperfusion in the frontal lobe has been documented in NPH patients using PET,13–15 single‐photon emission computed tomography (SPECT),16–18 and perfusion‐weighted magnetic resonance imaging (MRI) 19. Therefore, it is possible that the frontal lobe is the anatomical substrate for the development of neurogenic urinary incontinence in NPH.…”
Section: Introductionmentioning
confidence: 99%
“…70,114) A voxel-based analysis study reported a significant CBF increase in the bilateral dorsolateral frontal and left mesiotemporal cortices after the tap test. 25) No increase of CBF after the tap test was also reported. 54B) The involvement of autoregulatory impairment is still controversial.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…Dumarey et al [10] reported that gait improvement after STT in patients with NPH is associated with a bilateral regional CBF increase in the dorsolateral frontal cortex and an increase in the left mesial temporal cortex. This patient could walk more rapidly and smoothly after STT, because of partial alleviation of NPH.…”
Section: Discussionmentioning
confidence: 98%